MODERN METHODS OF TEACHING ENGLISH: FROM TRADITIONAL TO INNOVATIVE APPROACHES - Amanullaeva Kamola Muminovna; Mukhiddinva Komila Gafurjonovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the evolution of English language teaching methods, from traditional to innovative approaches. Particular attention is given to the analysis of grammar-translation, direct, audio-lingual, communicative, and reading- based methods, as well as author-developed approaches tailored to individual learner needs. The role of information technologies in transforming language education is highlighted, emphasizing their contribution to personalization and interactivity. Based on comparative analysis, the article offers recommendations for effectively combining classical and modern methodologies to enhance English language teaching in the context of globalization and digitalization in education.